The legal status of victims of international crimes within the framework of the International Criminal Court - خازم, نور الدين; عبد الله , علي (Latakia University Journal - Economic and Legal Sciences Series, 2021)
Since the last decade of the twentieth century, the issue of the rights of victims of international crimes has become one of the most controversial and controversial topics, and has received great attention at the national and international levels. It was necessary to work on the creation of international judicial bodies whose mission is to track international crimes committed, apply their own legal rules, and establish them. The subject of effective implementation, the protection and redress of the victims who have fallen victim to these crimes and the guarantee of all the rights assigned to them and their participation, independently of the state to which they belong, in claiming these rights. The current research aims to clarify the role of the International Criminal Court and its contribution to dedicating the rights of victims of international crimes and ensuring their fulfillment and obtaining a legal status for them at the national and international levels as a permanent international judicial body whose primary objective is to punish the perpetrators of international crimes and to secure mechanisms to protect the rights of victims in accordance with the provisions of the statute of this court . International crime is considered one of the most heinous and most dangerous forms of crime, and the logic of criminal justice requires a balance between the rights of the accused and their victims according to the legal status established for both parties, and this problem raises many questions. Despite the many advantages enjoyed by victims of international crimes, and despite the achievements that have been made at the national and international levels, in the context of recognizing a legal status for victims of international crimes, which guarantees them a broader scope to participate in the various stages of the judicial process, this was not enough. In certain cases, in order to achieve the primary objective of ensuring that the rights of victims of international crimes are fulfilled and protected.